2015
DOI: 10.1002/bit.25486
|View full text |Cite
|
Sign up to set email alerts
|

Shear stress upregulates IL‐1β secretion by Chlamydia pneumoniae‐ infected monocytes

Abstract: Infectious agents are increasingly implicated in the development and progression of chronic inflammatory diseases. Several lines of evidence suggest that the common intracellular respiratory pathogen, Chlamydia pneumoniae contributes to the well-established risk factors of atherosclerosis but the exact mechanism is not well understood. It is believed that C. pneumoniae-infected monocytes travel from the lung to the atherosclerotic foci, during which the cells experience mechanical stimuli due to blood flow. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
(33 reference statements)
1
2
0
Order By: Relevance
“…Monocytes infected with heat-killed chlamydial EBs show similar viability pattern to those of monocytes infected with live organisms with decrease in viability as early as 3 days ( Figure 1A ). Using confocal microscopy, we observed that at least 80% of the cells were infected and, consistent with our previous findings, the size of the inclusions ranged from very small to large inclusions (3–30 μm), and the cells contained a variable number of inclusions ( Figure 1B ) ( Cheeniyil et al, 2015 ). Interestingly, C. pneumoniae can be seen outside cells in the matrices at the end of 1 week possibly due to the release of C. pneumoniae inclusions, which correlates with the decrease in viability of infected cells in 7 days.…”
Section: Resultssupporting
confidence: 90%
“…Monocytes infected with heat-killed chlamydial EBs show similar viability pattern to those of monocytes infected with live organisms with decrease in viability as early as 3 days ( Figure 1A ). Using confocal microscopy, we observed that at least 80% of the cells were infected and, consistent with our previous findings, the size of the inclusions ranged from very small to large inclusions (3–30 μm), and the cells contained a variable number of inclusions ( Figure 1B ) ( Cheeniyil et al, 2015 ). Interestingly, C. pneumoniae can be seen outside cells in the matrices at the end of 1 week possibly due to the release of C. pneumoniae inclusions, which correlates with the decrease in viability of infected cells in 7 days.…”
Section: Resultssupporting
confidence: 90%
“…We observed that an MOI 1 was sufficient to see bacteria in >90% of cells, and within 8 h of infection, chlamydia was visible ( Fig. 1A ) 20 . It has previously been shown that C. pneumoniae infection increases the adhesion of monocytes to endothelium under static conditions, though it is now well established that the mechanics of adhesion under physiological flow conditions can be very different 21 .…”
Section: Resultsmentioning
confidence: 81%
“…We evaluated the effect of C. pneumoniae infection under flow on the interaction monocytes with endothelial cells and also the major endothelial adhesion receptor, E-selectin. All experiments were performed on monocytes infected for 8 h during which infection is established and a strong proinflammatory response is observed in vitro 20 . We perfused monocytes at a shear stress of 1 dyn/cm 2 for 5 min over E-selectin and TNFα-activated aortic endothelium, and assessed the number of rolling cells per unit time.…”
Section: Resultsmentioning
confidence: 99%